The Effect of Solvency on Profitability (Analysis Study on Manufacturing Companies in the Textile and Garment Sub-Sector Listed on the Indonesia Stock Exchange for the 2015-2019 Period) - Haviza, Riza (International Journal Labs, 2025)
This study aims to analyze the effect of profitability on solvency. based on secondary data in the form of annual financial reports using the sample method purposive sampling and multiple linear regression analysis method. This study consists of Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Long-term Debt to Equity Ratio (LDER) on solvency and Return on Assets (ROA) and Return on Equity (ROE) on profitability. The results can be concluded that solvency has an effect on profitability. The multiple linear regression analysis method is utilized to determine the relationships between these variables. The study's findings indicate a significant impact of solvency on profitability, highlighting how the management of debts and long-term liabilities influences a company's ability to generate returns. Additionally, this research underscores the importance of maintaining a balanced financial structure to achieve optimal profitability. By bridging the gap between solvency and profitability, the study provides valuable insights for stakeholders in decision-making processes related to financial planning and corporate strategies. These findings have practical implications for financial managers, as they emphasize the critical role of efficient solvency management in enhancing profitability and ensuring sustainable growth for organizations in competitive markets.